Engaging homelessness: Facilitating change through architectural intervention - Louw, Christopher (School of Architecture, Planning and Geomatics, 2018)
This dissertation engages with the issue of homelessness in the City of Cape Town. It makes use of existing literature and research on homelessness to frame the severity of the issue. Furthermore, it surfaces the lived experience of homelessness through first-hand accounts of living on the street, highlighting the challenges faced and survival strategies implemented by homeless individuals. The response focuses in part to meet the immediate needs of homeless individuals by creating a safe zone in which the activities of the home can be carried out. Furthermore, the intent is to engage with the homeless population across a range of thresholds, allowing them the autonomy to filter into a newly facilitated network that works with existing infrastructure to guide individuals on a journey off the street. The Dissertation culminates in a speculative design project near the fringe of Cape Town's CBD. The project deals with an undeveloped parcel of land, as well as the addition to and alterations of an existing Salvation Army building.